Analysis of Students' Mathematical Problem-Solving Skills in Terms of Math Anxiety Levels - Musodiqoh, Ummu Atiyatul; Nurbaiti, Idhata; Gunawan; Jaelani, Anton; Jazuli, Akhmad (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze students' mathematical problem-solving skills based on the level of math anxiety they experience. Math anxiety is a psychological factor that can affect students' academic performance in mathematics, especially in that require problem solving. The research method is qualitative with a descriptive approach. Data collection was carried out through tests, questionnaires, and interviews. The results of the math anxiety questionnaire categorized students into high, medium, and low categories. Respondents were collected by purposive sampling from each category of math anxiety. Data analysis consists of reduction, data presentation, and conclusion. The results showed that students with low math anxiety were able to solve problems more systematically and flexibly, while students with high math anxiety tended to have difficulty understanding problems and designing solution strategies. Students in the math anxiety category are having difficulty in implementing a completion plan and providing the right conclusions. These findings confirm that math anxiety has a significant impact on students' mathematical problem-solving skills. Abstrak: Penelitian ini bertujuan untuk menganalisis kemampuan pemecahan masalah matematika siswa berdasarkan tingkat kecemasan matematika yang dialaminya. Kecemasan matematika merupakan faktor psikologis yang dapat mempengaruhi prestasi akademik siswa dalam matematika, terutama dalam memecahkan masalah. Metode penelitiannya bersifat kualitatif dengan pendekatan deskriptif. Pengumpulan data dilakukan melalui tes, kuesioner, dan wawancara. Hasil kuesioner kecemasan matematika mengkategorikan siswa ke dalam kategori tinggi, sedang, dan rendah. Responden dikumpulkan dengan purposive sampling dari setiap kategori kecemasan matematika. Analisis data terdiri dari reduksi, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa siswa dengan kecemasan matematika rendah mampu memecahkan masalah secara lebih sistematis dan fleksibel, sedangkan siswa dengan kecemasan matematika tinggi cenderung mengalami kesulitan memahami masalah dan merancang strategi solusi. Siswa dalam kategori kecemasan matematika mengalami kesulitan dalam menerapkan rencana penyelesaian dan memberikan kesimpulan yang tepat. Temuan ini menegaskan bahwa kecemasan matematika memiliki dampak yang signifikan pada keterampilan pemecahan masalah matematika siswa.